2018
DOI: 10.1155/2018/4527203
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen Release from Poly(ethyl cyanoacrylate) Nanoparticles Prepared by Semicontinuous Heterophase Polymerization

Abstract: Ibuprofen-loaded poly(ethyl cyanoacrylate) nanoparticles were prepared by semicontinuous heterophase polymerization of ethyl cyanoacrylate in the presence of ibuprofen; different surfactant concentration, pH, and temperature were used. Particle size was measured by quasi-light scattering and transmission electron microscopy, while the amount of drug released was determined by UV spectroscopy. Nanoparticles with diameters between 10 and 58 nm, loaded with ibuprofen, were obtained. The smallest particles and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The Weibull equation can be applied to almost all types of dissolution curves. Here k w is the Weibull constant related to the inverse of the time required to release 63.2% of the drug, and n indicates the shape of the curve [ 35 , 36 ]. …”
Section: Resultsmentioning
confidence: 99%
“…The Weibull equation can be applied to almost all types of dissolution curves. Here k w is the Weibull constant related to the inverse of the time required to release 63.2% of the drug, and n indicates the shape of the curve [ 35 , 36 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Each solution was transferred to a 10 mL volumetric flask and further diluted with deionized water. The maximum UV absorbance peak of the IBU was observed at 264 nm, [ 20 ] thus 264 nm was selected as the wavelength for this test. The concentrations of the solutions were plotted on the horizontal axis (X), while the corresponding absorbance values were plotted on the vertical axis (Y).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to other drug delivery systems such as liposomes and polymeric nanoparticles, ZrO 2 nanostructures have been shown to have longer drug release profiles, which may be advantageous for certain applications. For example, a study found that NP micelle loaded with doxorubicin exhibited sustained release of the drug over a period of 48 h [172], while another study found that the release of the ibuprofen from polymeric nanoparticles occurs during the initial 80-120 min [173]. In other investigations, the loading and release efficiencies of a wide range of drugs such as ibuprofen, N-acetyl-l-cysteine, vancomycin, gentamicin, nitrofurantoin, and indomethacin characterized by a large range of polarity, molecular weight, and various functional groups were studied [25].…”
Section: Comparison Of the Drug Release Profiles Of Zro 2 Nanostructu...mentioning
confidence: 99%